A genome-wide association study of social trust in 33,882 Danish blood donors - Celia Burgos Sequeros; Thomas Folkmann Hansen; David Westergaard; Ioannis Louloudis; Sebastian Kalamajski; Timo Röder; Palle Duun Rohde; Michael Schwinn; Line Harder Clemmensen; Maria Didriksen; Mette Nyegaard; Henrik Hjalgrim; et al. (Scientific Reports, 2024)
Abstract Social trust is a heritable trait that has been linked with physical health and longevity. In this study, we performed genome-wide association studies of self-reported social trust in n = 33,882 Danish blood donors. We observed genome-wide and local evidence of genetic similarity with other brain-related phenotypes and estimated the single nucleotide polymorphism-based heritability of trust to be 6% (95% confidence interval = (2.1, 9.9)). In our discovery cohort (n = 25,819), we identified one significantly associated locus (lead variant: rs12776883) in an intronic enhancer region of PLPP4, a gene highly expressed in brain, kidneys, and testes. However, we could not replicate the signal in an independent set of donors who were phenotyped a year later (n = 8063). In the subsequent meta-analysis, we found a second significantly associated variant (rs71543507) in an intergenic enhancer region. Overall, our work confirms that social trust is heritable, and provides an initial look into the genetic factors that influence it.